Dietary low levels of Eucommia ulmoides leaf extracts: effects on antioxidant capacity, immunity, and cecal microbiota in lipopolysaccharide-challenged broilers - Zhang, Jinliang; Chai, Lei; Guo, Yan; Han, Jincheng; Yang, Guangli (Frontiers in Microbiology, 2025)
BackgroundEnvironmental stimuli exerts detrimental effects on health and production performance during intensive animal production with ensuing serious economic consequences. This study aimed to investigate the effects of dietary low levels of Eucommia ulmoides leaf extracts (EULE) on antioxidant capacity, immunity, and cecal microbiota in lipopolysaccharide (LPS) -challenged broilers.Methods and ResultsIn this study, a total of 400 21-day-old Ross 308 male broilers were divided into 5 groups, with 8 replicates per group and 10 birds per replicate. They were fed a basal diet (CON group and LPS group) or a basal diet supplemented with 100, 200, or 300 mg/kg EULE (EULE100, EULE200, and EULE300 groups) for 10 consecutive days. The results showed that growth performance and relative organ weights were not affected by either LPS injection or EULE supplementation (p < 0.05), but dietary supplementation with EULE decreased the increased relative organ weights in LPS-induced broilers. LPS challenge decreased the level of catalase (CAT), Faecalibacterium, and increased the level of Interleukin 4 (IL-4), which were improved by EULE (p < 0.05). Furthermore, EULE200 and EULE300 reduced the levels of IL-1β, IL-2 and IL-6 in LPS-induced broilers. EULE300 significantly decreased the serum malondialdehyde (MDA) level and increased the level of total antioxidant capacity (T-AOC), and reduced the proportion of harmful genera Erysipelatoclostridium in cecum.ConclusionThis study emphasizes that dietary inclusion EULE, even low levels (100, 200, or 300 mg/kg), can exhibit significant anti-inflammatory and anti-oxidation effects, modulate cecal microbiota structure and restore cecum barrier function caused by LPS stimulation.